Studying the Nesting Biology of Golden Eagles by Use of Trap Cameras - Ivaylo D. Angelov (Пернатые хищники и их охрана)
Trap camera was installed in an active nest of Golden Eagles (Aquila chrysaetos) in Eastern Rhodopes, Bulgaria. The recordings encompassed 45 days in June and July and the camera took 12 900 photos, from the time when the single chick was ca. 32 days old until its fledging. 84 food deliveries were recorded, with the prey identified in 76 of them.